On one homogeneity test based on the kernel-type estimators of the distribution density - Babilua, P.; Nadaraya, E. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
We construct a homogeneity test based on the kernel-type estimators of the distribution density and investigate its consistency.